Men and Women in Suicide Notes: A Corpus-Based Rhetorical Moves Analysis - Jeanyfer Tanusy (Journal of Language and Literature, 2022)
Research on suicide notes has always focused on proving whether the notes are genuine or simulated. There are still very few studies on suicide notes that focus on the genders of the writer and the influence of genders in this type of letter. This research aims to examine the suicide notes in two corpora—one corpus written by males and the other by females—using two different theories. Swales’ move-structure theory is used to see the pattern of occurrence of the rhetorical moves to establish a generic structure of the notes in the two corpora, and Bhatia’s communicative purpose theory is used to see what purposes of communication are dominant in the notes. The notes are analyzed based on the gender of the writers to also examine whether gender plays a role in the use of language, especially for personal communication. The study uses a mixed-method approach, in which a corpus software AntConc is used in the quantitative design to gather more comprehensive data, and linguistic theories are used in the interpretation of the data. The analysis shows that there are differences in the dominant recurring moves and communicative purposes in the two corpora, which suggests the role of gender in determining language use in personal communication. The result of this study is hoped to add to the literature of the study of gender as well as in the broader area of discourse analysis and sociolinguistics.